EXTRACTION AND PURIFICATION OF β-galactosidaseFROM NEW BORN SHEEP BRAIN. - Abed, Ali (Iraqi Journal of Science, 2024)
β -galactosidase enzyme was extracted from the new born sheep brain by ninesolutions, It was found that the0.2 M sodium acetate and 0.2M NaCl give a highestspecific activity of crude enzyme. This enzyme was concentrated by four methods,includes: concentration by ammonium sulfate (20-60%); old acetone; ethanol (30%-60%) and by ultra filtration. It was found that the cold acetone was the better. Thepurification folds were about 124.78 times and yield about 77.39%. The molecularweight of this enzyme about 185.942 Kilo Dalton.